A critical analysis of horn of Africa’s drought-related metaphors: A socio-cognitive approach - El-Masry, Menna Mohamed Salama (Research Journal in Advanced Humanities, 2023)
The paper regulates a corpus-based analysis of Horn of Africa’s drought-related metaphorical schemas presented in 17 selected reports and appeals published in the official homepages of UNICEF and OCHA in the time span (2021-2023). The study follows Hart’s (2008 & 2010) theoretical framework of socio-cognitive critical metaphor analysis (SCCMT) which connects blending integration theory (BT) and the critical, social and ideological tenets of critical discourse analysis (CDA). The findings of the study show three recurrent metaphorical integration networks in the selected corpus and they are: DROUGHT is A KILLING MONESTER, DROUGHT is WAR/STRUGGLE and UNICEF/OCHA are BUILDERS/ANIMATE AGENTS. Consequently, some emergent scenarios are activated such as: fear, instability, blame, hope and ideological distinction of US and THEM, THE POOR and THE RICH, AFRICA and AMERICA & EUROPE. Moreover, four topoi are motivated: “topos of danger”, “topos of displacement”, “topos of number” and” topos of hope”. These topoi are entrenched in the selected corpus, thus explicating the conventionality of metaphor.